Bird Diversity: The Potential of Avitourism Reserves for Bird Conservation in Curup Tenang, South Sumatera, Indonesia - Fajar Islam Sitanggang; Mokhamad Asyief Khasan Budiman; Andy Afandy (Jurnal Biodjati, 2020)
Birds have a fairly wide living habitat, including water-falls. Curup Tenang is a waterfall tourism site which has a wildlife habitat suitable for birds. In The Curup Tenang tourism site, the number of visitors has decreased over years. Birds are one of the wildlife animals that have ecological values, potential tourism, and cultural values. The diversity of birds in this tourist location have not been recorded. Meanwhile, by increasing knowledge and data-bases regarding the diversity of birds in this area can be an addi-tional reference for the development strategy in the Curup Tenang tourism site so that it becomes a distinctive attraction for visitors. This study aimed to determine the diversity of birds that never been recorded before and to conduct a potential support of avitourism activities. The results of this study can be used as a guideline to study the potential of avitourism. The diversity of birds found in Curup Tenang consisted of forty-eight species belong to twenty-seven families, while three of them cited as protected bird species. This study concluded that Curup Tenang contains a high diversity of birds and it has a great potential to be developed into an attraction of tourism.Â